Six of crows - Bardugo, Leigh (New York : Henry Holt and Co., 2015)
"Six dangerous outcasts. One impossible heist. Kaz's crew is the only thing that might stand between the world and destruction--if they don't kill each other first"--Provided by publisher.
School Library Journal starred, September 2015
Bulletin of the Center for Children's Books starre, November 2015
Pub Weekly, July 2015
Kirkus Starred, July 2015
Booklist, August 2015
New York Times, October 2015
Keywords: Brigands and robbers -- Juvenile fiction; Robbers and outlaws -- Fiction; Thieves -- Fiction; Fantasy fiction